Dynorphin/kappa opioid receptor system regulation on amygdaloid circuitry: Implications for neuropsychiatric disorders - Limoges, Aaron; Yarur, Hector E.; Tejeda, Hugo A. (Frontiers in Systems Neuroscience, 2022)
Amygdaloid circuits are involved in a variety of emotional and motivation-related behaviors and is impacted by stress. The amygdala expresses several neuromodulatory systems, including opioid peptides and their receptors. The dynorphin (DYN)/kappa opioid receptor (KOR) system has been implicated in the processing of emotional and stress-related information and is expressed in brain areas involved in stress and motivation. Dysregulation of the DYN/KOR system has also been implicated in various neuropsychiatric disorders. However, there is limited information about the role of the DYN/KOR system in regulating amygdala circuitry. Here, we review the literature on the (1) basic anatomy of the amygdala, (2) functional regulation of synaptic transmission by the DYN/KOR system, (3) anatomical architecture and function of the DYN/KOR system in the amygdala, (4) regulation of amygdala-dependent behaviors by the DYN/KOR system, and (5) future directions for the field. Future work investigating how the DYN/KOR system shapes a wide range of amygdala-related behaviors will be required to increase our understanding of underlying circuitry modulation by the DYN/KOR system. We anticipate that continued focus on the amygdala Dyn/KOR system will also elucidate novel ways to target the DYN/KOR system to treat neuropsychiatric disorders.